Phase 1b/2 Study of Carfilzomib, Pomalidomide, and Dexamethasone (KPd) in Patients (Pts) with Lenalidomide-Exposed and/or -Refractory but Proteasome Inhibitor (PI)-Naive or -Sensitive Multiple Myeloma: A Multiple Myeloma Research Consortium Multi-Center Study - Rosenbaum, Cara A.; Kukreti, Vishal; Zonder, Jeffrey; Lebovic, Daniel; Zimmerman, Todd; Berdeja, Jesus G.; McDonnell, Kathryn; Waite-Marin, Jessica; Griffith, Kent A.; Jakubowiak, Andrzej (Blood, 2014)
Introduction Benefits of carfilzomib (CFZ) and pomalidomide (POM) in heavily pretreated relapsed and refractory multiple myeloma (RRMM) are well established. The combination of these agents with dexamethasone (DEX) showed very promising activity in advanced disease after a median of 5 lines of prior therapy, including pts refractory to both bortezomib (BTZ) and lenalidomide (LEN) (Shah et al; ASH 2013:122[21]). The activity of this regimen in less-heavily pretreated pts is not known. In this phase 1b/2 study, we evaluate a similar KPd combination in pts in earlier stages of the disease, including a primary study population of PI-naive or -sensitive pts who were previously treated with LEN and/or are LEN-refractory. The primary objectives of the study are to establish the maximum tolerated dose (MTD) of KPd and provide preliminary assessment of the regimen’s activity in early relapse. Methods PI-naive or -sensitive pts with RRMM who have failed ≥1 prior therapies are eligible; LEN-refractory disease (progressing on LEN or within 60 days of discontinuation) is required for the 2nd line, or LEN exposure and/or progression on LEN maintenance for the 3rd or later line of treatment. The phase 1b dose escalation follows the TITE-CRM algorithm with pts receiving 3–4 mg POM PO (days 1–21), 20–36 mg/m2CFZ (given IV on days 1, 2, 8, 9, 15, 16 in cycles 1–8 and on days 1, 2, 15, 16 in cycles 9+), and 40/20 mg DEX PO weekly (cycles 1–4/5–8; for all dose levels) in 28-day cycles. Forty pts are planned for phase 1b, and 30 pts are planned to be treated at the MTD across phases 1 and 2. The primary objective of the phase 1b study is to evaluate the safety of KPd and identify the MTD. The primary objective of the phase 2 study is to assess response rates at the MTD after 4 cycles, defined per IMWG criteria with the addition of near complete response (nCR). As an exploratory end point, the study will evaluate KPd activity in an additional 30 pts refractory to PIs or POM. Results As of July 30, 2014, the study has enrolled 27 pts in the phase 1b study; 4 pts at level 1 (20 mg/m2 CFZ, 3 mg POM), 9 pts at level 2 (20 mg/m2 CFZ, 4 mg POM), and 14 pts at level 3 (20/27 mg/m2 CFZ, 4 mg POM). Pts had a median age of 63 (range, 51–79) and a median of 2 prior treatments (range, 1–6). Twenty-three pts met criteria for the primary study population of PI-naive/sensitive and LEN- refractory/exposed; 15 were LEN-refractory, and an additional 8 had progressed on LEN maintenance. Toxicity data were available for 26 pts, of whom 25 had completed ≥1 cycle. Twenty pts were DLT-evaluable (7 pts did not receive all scheduled cycle 1 doses and were thus not evaluable for DLTs, including 1 pt who was replaced due to noncompliance). There were 5 DLTs, all due to delay of cycle 2 initiation: 4 cases of grade (G) 3 neutropenia and 1 G4 thrombocytopenia on day 1 of cycle 2. The MTD has not yet been reached; current enrollment is at dose level 3 (20/27 mg/m2 CFZ, 4 mg POM, 40 mg DEX). Hematologic toxicities were reversible and included 23% neutropenia, 19% thrombocytopenia, and 27% anemia (all grades). Most common nonhematologic toxicities (all grades) were infection (54%), fatigue (50%), and dyspnea (35%). KPd-related G1/2 peripheral neuropathy (PN) was reported in 35% of pts; 1 pt with G2 sensory PN elected to come off study during cycle 7 while in nCR. After a median of 5 cycles (range, 1–17), response rates in all 25 evaluable pts who completed ≥1 cycle were 72% ≥partial response (PR), 28% ≥very good PR (VGPR), 12% CR/nCR; clinical benefit rate (CBR; ≥minor response) was 84%. In the primary study population of PI-naive/sensitive and LEN-refractory/exposed pts, 77% achieved ≥PR, 27% ≥VGPR, 9% CR/nCR; CBR was 91%. Responses were rapid, with 52% of pts achieving ≥PR after 1 cycle and improving with treatment; after 4 cycles, ≥PR was 79%, and CBR was 89% in 19 evaluable pts. After a median of 9.5 months of follow-up, 11 pts have progressed, and 2 died; 14 are still on treatment. Conclusion The KPd combination is overall well tolerated and highly active in RRMM, with 78% ≥PR in a primary study population of PI-naive/sensitive but LEN-refractory/exposed pts. Accrual is ongoing to determine the MTD, and enrollment will continue into phase 2 at the MTD. Updated toxicity and efficacy data based on cytogenetic risk will be presented. These results represent the first reported use of KPd to treat less-heavily pretreated pts with mostly LEN-refractory MM and/or progression on LEN maintenance in the era of increased use of extended LEN treatment. Rosenbaum:Celgene: Speakers Bureau. Off Label Use: Carfilzomib is approved in the United States for the treatment of patients with multiple myeloma who have received at least two prior therapies including bortezomib and an immunomodulatory agent and have demonstrated disease progression on or within 60 days of completion of the last therapy. The study presented here enrolled patients with multiple myeloma who had failed ≥1 prior regimen; patients could be proteasome inhibitor-naïve or –sensitive and lenalidomide-exposed and/or -refractory. Patients received carfilzomib in combination with pomalidomide and dexamethasone.. Kukreti:Onyx: Research Funding; Millennium Pharmaceuticals: Research Funding. Zonder:Bristol-Myers Squibb: Honoraria; Celgene: Honoraria, Research Funding. Zimmerman:Celgene: Honoraria; Onyx: Honoraria. Jakubowiak:Onyx: Consultancy, Honoraria, Membership on an entity’s Board of Directors or advisory committees, Speakers Bureau; Novartis: Honoraria, Membership on an entity’s Board of Directors or advisory committees; Millennium: Consultancy, Honoraria, Membership on an entity’s Board of Directors or advisory committees; Celgene: Consultancy, Honoraria, Membership on an entity’s Board of Directors or advisory committees, Speakers Bureau; Bristol-Myers Squibb: Consultancy, Honoraria, Membership on an entity’s Board of Directors or advisory committees; SkylineDx: Honoraria, Membership on an entity’s Board of Directors or advisory committees; Janssen: Consultancy, Honoraria, Membership on an entity’s Board of Directors or advisory committees, Speakers Bureau.